New Advances in Stem Cell Therapy for Osteonecrosis of the Femoral Head - Zhou, Wei; Qu, Ming; Lv, Yajie; Zhu, Jinyu (Current Stem Cell Research & Therapy, 2019)
Osteonecrosis of the femoral head (ONFH) is a common refractory orthopedic disease with multiple etiologies that more frequently occurs in middle-aged and young people. ONFH is the main cause of hip replacement in young patients. Since Professor Hernigou first reported the use of stem cells in the treatment of early stage ONFH, a large number of studies have demonstrated the potential of stem cells in the treatment of adult patients with ONFH. With the rise of interdisciplinary stem cell therapy combined with platelet-rich plasma therapy, gene therapy or other methods have gradually attracted the attention of researchers. This article summarizes the current advances in stem cell therapy for ONFH, as well as the problems and challenges, which may provide reference for further research.
Keywords: osteonecrosis of the femoral head